Impact of Cell Texturing Quality on Cell to Module Losses. (August 2015) - Schneider, Andreas; Harney, Rudolf; Koch, Simon
Abstract: This work is related to a detailed study on the influence of the quality of solar cell texturing on the electrical performance after encapsulation. The effect of texturing on cells front side reflectance was studied for alkaline texturing on Cz wafer materials and processes, acidic textured Cz wafers as well as polished Cz wafers and correlated to the electrical characteristics after encapsulation. The electrical performance on module level was studied indoor at STC (standard test conditions) with varying incident light angles and outdoor during one year of outdoor exposure at a location in southern Germany. To consider for optical effects of glass surface on module performance solar glass with various deep surface texture resp. a flat surface (float glass) were processed and characterized. We show that the degree of texturing hence the front side cell reflection has a small influence on the electrical performance after encapsulation with no measurable incident light angle dependency. Furthermore do we show that even for various textured glasses the cell texturing has no effect on the module performance, neither at STC nor at varying incident light angles. The annual electrical yield study revealed even a better performance for the acidic textured cell modules if compared to the alkaline (hence well textured) cell modules.